THE EARLY VISÉAN (CARBONIFEROUS) CONODONTS FROM THE SAOURA VALLEY, ALGERIA - Nemyrovska T.I.; Perret-Mirouse M.-F.; Weyant M. (My University, 2006)
The present study reports on conodonts from the El Hariga Formation (lower Viséan) of the Saoura Valley, Algeria. This formation overlies the Hassi Sguilma Formation with the latest Tournaisian conodont assemblage with Scaliognathus anchoralis and it is overlain by the Mazzer Formation with the mid-Viséan conodont fauna with Gnathodus bilineatus. The conodont assemblage of the El Hariga Formation contains the latest Tournaisian gnathodontids and the Viséan Pseudognathodus and unornamented early Viséan species of Lochriea. A new species, Lochriea saharae, a probable earliest representative of Lochriea is described. Its relationships to L. cracoviensis, L. commutata and Bispathodus stabilis are discussed.
Keywords: ALGERIA; BIOSTRATIGRAPHY; CARBONIFEROUS; CONODONTS; SAOURA VALLEY; TAXONOMY; VISÉAN; Палеозой::Каменноугольная::Средний::Визейский; Paleozoic::Carboniferous::Visean